1994
DOI: 10.1016/0735-1097(94)90030-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical procedure for the cure of atrioventricular junctional (“AV node”) reentrant tachycardia: Anatomic and electrophysiologic effects of dissection of the anterior atrionodal connections in a canine model

Abstract: The atrionodal connections closest to the His bundle are the preferred route of conduction through the AV node during normal AV or VA conduction. Destruction of these connections modifies AV node conduction. The surgical procedure selectively interrupts these connections, and this interruption is likely to be the mechanism of cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Accordingly, the effects of anterior (type A) and posterior (type B) dissection were examined in experimental animals. 62,63 These studies showed some degree of damage to the AV node in animals undergoing type A dissection but in more than 40% of cases this damage was minor. Moreover, there was only mild impairment of anterograde AV conduction.…”
Section: Av Junctional Re-entrant Tachycardiamentioning
confidence: 96%
“…Accordingly, the effects of anterior (type A) and posterior (type B) dissection were examined in experimental animals. 62,63 These studies showed some degree of damage to the AV node in animals undergoing type A dissection but in more than 40% of cases this damage was minor. Moreover, there was only mild impairment of anterograde AV conduction.…”
Section: Av Junctional Re-entrant Tachycardiamentioning
confidence: 96%
“…Some investigators arbitrarily divided these nondiscrete AV nodal inputs into the so-called fast pathway, slow pathway, and intermediate pathway. McGuire et al suggested that the atrionodal connection closest to the His bundle was the preferred route of conduction through the AV node during normal AVor VA conduction, and that part of slow AV nodal pathway may lie outside the compact AV node [12,13]. Previous animal studies demonstrated that the antegrade conduction over the slow pathway existed in all normal hearts with or without AVNRT, but did not become manifest because propagation over the fast pathway reached the AV node first [11,14].…”
Section: Antegrade Av Nodal Inputsmentioning
confidence: 96%
“…However, the propagation of the wavefronts in the other two cases could not spread directly toward the apex of Koch's triangle during atrial pacing with shorter CLs, but instead appeared to approach the AV nodal region via the posterior "slow" pathway input. This particular phenomenon may be caused by: 1) previous ablation lesions, 2) local fibrosis due to the older age or, 3) local functional block due to a negative balance of the source and sink [12,13,16].…”
Section: Antegrade Av Nodal Inputsmentioning
confidence: 97%
“…Stimulation from the distal coronary sinus was often associated with pacing failure (due to the high stimulation threshold) or simultaneous pacing of the left atrium and the left ventricle.' Thus, selective left atrial pacing from the distal coronary sinus was possible in only 6 cases (9)(10)(11)(12)19, and 20).…”
Section: Electrophysiological Studymentioning
confidence: 98%